-31=-2x+3

Simple and best practice solution for -31=-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -31=-2x+3 equation:


Simplifying
-31 = -2x + 3

Reorder the terms:
-31 = 3 + -2x

Solving
-31 = 3 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-31 + 2x = 3 + -2x + 2x

Combine like terms: -2x + 2x = 0
-31 + 2x = 3 + 0
-31 + 2x = 3

Add '31' to each side of the equation.
-31 + 31 + 2x = 3 + 31

Combine like terms: -31 + 31 = 0
0 + 2x = 3 + 31
2x = 3 + 31

Combine like terms: 3 + 31 = 34
2x = 34

Divide each side by '2'.
x = 17

Simplifying
x = 17

See similar equations:

| 21=4x-9-1x | | a+14=8 | | -12-3x=-24-6x | | 2(y+4)=18 | | 6u-12u= | | -5(n+3)-7+8n= | | j/3=2/5 | | -5(z+3)+4(3z-4)=6(z-3)+14 | | 6(3-2x)=1-(2x-1) | | 4-7+8=4(n)+4(n) | | -2x+9=-3x+29 | | 7x-16=6x-12 | | Z=5+2i | | -4(x-2)=4(2x+5) | | -log*(x)=0.85 | | 20x+25=19x+29 | | a(1+2a)-a(4a-5)= | | 25x^4=61x^2-36 | | 12(h-1)=6h+4+2 | | -2m+0=180(-49y) | | 198=x+2*x*2 | | 14+5(2x+2)=-5 | | 8+3x+4=10 | | 198=x+2+x+2 | | 7-2n-n=-14 | | 12/42=4w/56 | | -2+0=180(-49y) | | w=3ab | | x/8.9=22 | | 2z+8=4z-4 | | 4(2x-5)=-2(7-3x) | | -150h=400 |

Equations solver categories